Sculpture and the creative process [videorecording] - Payne, John.; Wanner, Jim. (Glenview, Ill. Crystal Productions, 1962)
Explores the creative process of the sculpture of Dale Lamphere. Discusses important considerations for anyone looking at a career as a sculptor. Provides an overview of the lost wax casting process.
VHS.
Dale Lamphere, sculptor.
Keywords: Lamphere, Dale; Sculpture -- Techniques; Sculpture -- Vocational guidance; Waxworks